2019
DOI: 10.5005/jp-journals-10078-1246
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Ocular Scarring in Glaucoma Filtration Surgery Using the Epigenetic Adjunct Suberoylanilide Hydroxamic Acid

Abstract: Aim The aim of this study is to assess the effectiveness of suberoylanilide hydroxamic acid (SAHA), a histone deacetylase inhibitor (HDI) with a broad spectrum epigenetic activity, in improving filtration bleb survival as an adjunct therapy to glaucoma filtration surgery (GFS) in the rabbit model. Materials and methods Eighteen New Zealand White rabbits underwent GFS in the left eye and were randomized to receive either a subconjunctival (SC) injection of 0.1 mL SAHA (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Clinically effective dosage of MMC is 0.02–0.4 mg/ml (0.002–0.04%) used intraoperatively 64 , 65 . Subconjunctival injection of SAHA (9.25 μg/ml and 50 μM) were given in New Zealand white rabbits to improve bleb survival and prevent fibrosis in Glaucoma filteration surgery 66 , 67 . Topically 25–350μM of SAHA has been administered in New Zealand white rabbits and Sprague–Dawley rats respectively, to prevent corneal haze/scarring post PRK 20 , 26 , 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinically effective dosage of MMC is 0.02–0.4 mg/ml (0.002–0.04%) used intraoperatively 64 , 65 . Subconjunctival injection of SAHA (9.25 μg/ml and 50 μM) were given in New Zealand white rabbits to improve bleb survival and prevent fibrosis in Glaucoma filteration surgery 66 , 67 . Topically 25–350μM of SAHA has been administered in New Zealand white rabbits and Sprague–Dawley rats respectively, to prevent corneal haze/scarring post PRK 20 , 26 , 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Methods of gene therapy involve increasing expressions of inhibitory genes and proteins in the cell cycle. Human p53 is a tumor suppressor gene that plays a key role in arresting cell cycle progression to allow DNA repair or inducing apoptosis if the damage is too extensive [ 172 ]. Many studies have demonstrated p53 as an active player in human Tenon’s fibroblast migration and growth [ 102 , 103 ].…”
Section: Strategies To Prevent Ocular Fibrosis Following Glaucoma Fil...mentioning
confidence: 99%